Core-shelled mesoporous CoFe2O4–SiO2 material with good adsorption and high-temperature magnetic recycling capabilities. (April 2018) - Li, Zhi'ang; Wang, Jianlin; Liu, Min; Chen, Tong; Chen, Jifang; Ge, Wen; Fu, Zhengping; Peng, Ranran; Zhai, Xiaofang; Lu, Yalin
Abstract: Residues of organic dye in industrial effluents cause severe water system pollution. Although several methods, such as biodegradation and activated carbon adsorption, are available for treating these effluents before their discharge into waterbodies, secondary pollution by adsorbents and degrading products remains an issue. Therefore, new materials should be identified to solve this problem. In this work, CoFe2 O4 –SiO2 core–shell structures were synthesized using an improved Stöber method by coating mesoporous silica onto CoFe2 O4 nanoparticles. The specific surface areas of the synthesized particles range from 30 m 2 /g to 150 m 2 /g and vary according to the dosage amount of tetraethoxysilane. Such core-shelled nanoparticles have the following advantages for treating industrial effluents mixed with dye: good adsorption capability, above-room-temperature magnetic recycling capability, and heat-enduring stability. Through adsorption of methylene blue, a typical dyeing material, the core–shell-structured particles show a good adsorption capability of approximately 33 mg/L. The particles are easily and completely collected by magnets, which is possible due to the magnetic property of core CoFe2 O4 . Heat treatment can burn out the adsorbed dyes and good adsorption performance is sustained even after several heat-treating loops. This property overcomes the common problem of particles with Fe3 O4 as a core, by which Fe3 O4 is oxidized to nonmagnetic α-Fe2 O3 at the burning temperature. We also designed a miniature of effluent-treating pipeline, which demonstrates the potential of the application. Graphical abstract: Image 1 Highlights: CoFe2 O4 –SiO2 core–shell-structured nanoparticles with a good adsorption ability are synthesized. The SiO2 shell has a microporous structure that improves the adsorption ability. The particles can be easily and completely collected using magnets, which avoids the secondary pollution problem. The particles are degradation resistant even after multiple cycles of burning to remove the adsorbed pollutants and recycling.